2016
DOI: 10.5812/aapm.33653
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Glasgow Coma Scale, Full Outline of Unresponsiveness and Acute Physiology and Chronic Health Evaluation in Prediction of Mortality Rate Among Patients With Traumatic Brain Injury Admitted to Intensive Care Unit

Abstract: BackgroundTraumatic brain injury (TBI) is a common cause of mortality and disability worldwide. Choosing an appropriate diagnostic tool is critical in early stage for appropriate decision about primary diagnosis, medical care and prognosis.ObjectivesThis study aimed to compare the Glasgow coma scale (GCS), full outline of unresponsiveness (FOUR) and acute physiology and chronic health evaluation (APACHE II) with respect to prediction of the mortality rate of patients with TBI admitted to intensive care unit.Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…The number of patients reported by each included study ranged from 35 16 to 1645. 15 For the purposes of this review, reports by Gorji and colleagues 16,25 and Hosseini and colleagues 26 of a single population of 80 patients were considered to be a single study. Likewise, reports of a single cohort by McNett and colleagues in 2016 27 and 2014 17 were considered to be a single study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of patients reported by each included study ranged from 35 16 to 1645. 15 For the purposes of this review, reports by Gorji and colleagues 16,25 and Hosseini and colleagues 26 of a single population of 80 patients were considered to be a single study. Likewise, reports of a single cohort by McNett and colleagues in 2016 27 and 2014 17 were considered to be a single study.…”
Section: Resultsmentioning
confidence: 99%
“…Of these studies, 25 described in-hospital mortality 7,14,23,24,29,33,35,36,38–41,15,42,45–47,49,16–22 as the end point, 5 investigated mortality only up to 2 weeks post-event, 25,26,28,37,38 and 11 studies explored longer-term mortality up to 3–6 months. 14,25,52,26,30–32,34,42,44,45 The mortality rate between included studies varied widely—from 7.8% 36 to 70% 28 —among studies where FOUR score was assessed within 24 h of admission. Studies using later time points of FOUR score assessment reported mortality within the above range (Supplementary Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…41 GCS is also a strong predictor of in-hospital mortality and poor neurological outcome. 32,42 We assessed functional outcome at discharge from the in-patient neuroscience stepdown unit while the aforementioned studies assessed functional outcome between 14-days to 6 months post-injury. While the association between injury severity and outcome in patients with moderate and severe TBI is well known, what we can conclude about initial injury severity and functional outcome in this sample is this: GCS could be a signal for subsequent functional outcome, but cannot supplant other important clinical factors.…”
Section: Glasgow Coma Scale Score Functional Outcomementioning
confidence: 99%
“…Traumatic brain injury (TBI) as a major health and socioeconomic concern, remains one of the main causes of mortality and morbidity among the cases with trauma worldwidethroughout the world (1-4). The incidence of TBI is rising especially in the developing countries with a significant financial annual burden due to more vehicle use.…”
Section: Introductionmentioning
confidence: 99%